Optimizing artificial insemination on swamp buffalo (Bubalus bubalis) through synchronization of estrus and ovulation - Sianturi, Riasari Gail; Purwantara, B; Supriatna, I; ., Amrozi; Situmorang, P (Indonesian Journal of Animal and Veterinary Sciences, 2012)
Artificial insemination (AI) program in swamp buffalo will be more efficient by implementing synchronization of estrus and ovulation. By synchronizing of ovulation, AI can be done at a fixed time schedule without concerning to estrus detection. Gonadotropin Releasing Hormone (GnRH) and human chorionic gonadotropin (hCG) have been used in protocols of estrus synchronization to induce ovulation. A study of AI in swamp buffalo was conducted on 83 buffaloes to evaluate the impact of protocol of estrus synchronization on reproductive efficiency of swamp buffalo. The three protocols used were Ovsynch (GnRH-PGF2Î±-GnRH-AI), convensional (PGF2a-PGF2a-AI) and Select-Synch (GnRH-PGF2a-AI). Inducing of ovulation were done by administration of GnRH or hCG after prostaglandin (PGF2Î±) injection. AI was done at 18 and 24 hour after the second GnRH injection (66 hours and 72 hours after PGF2Î± injection) for Ovsynch method and 72 hours after the last PGF2Î± injection for convensional and Select-Synch methods. Parameters observed were percentage of estrus and pregnancy from the three estrus synchronization protocols and the differences were analysed by statistics. All of buffaloes (100%) in the three synchronization protocols showed estrus behavior prior to AI. The percentage of pregnancy was 64.71; 77.14 and 83.87% for the Ovsynch, convensional and Select-synch respectively and there was no significantly different (P > 0.05) among the three protocols. hCG administration after the last PGF2Î± also did not affect pregnancy rate, ie: 76.47 vs 77.78% (with hCG vs without hCG) for the convensional and 88.24 vs 78.57% for the Select-Synch. It is concluded that the synchronization of estrus protocols in this study can synchronize the estrous and ovulation and AI can be done in a fixed-timed and could reach better pregnancy rate of swamp buffalo. Key Words: Swamp Buffalo, Synchronization, Estrus, Ovulation, AI